Ontological and Meta–Physical Aspect of Information - Łapiński, Jacek (Kwartalnik Naukowy Fides et Ratio, 2021)
The publication contains analyzes on the understanding of information in terms of quantitative and qualitative, objective and subjective aspects, the way it works and the role played in the process of morphogenesis.The aim of the publication is an attempt to define the ontological status of information and to indicate possible sources of its origin. The qualitative, not quantitative, aspect of the information is important. Determining what, in its qualitative essence, information is, what a being is, will allow to create the necessary premises to try to confirm or deny the thesis that information is a fundamental and fully real causative and functional factor of morphogenesis, as well as to verify the correctness of the hypothesis about a specific, fundamental, related to the action of God, the source of information origin.